Debt sustainability and the fiscal reaction function: Evidence from MIST countries - Lawrence Ogbeifun; Olatunji Abdul Shobande (Future Business Journal, 2020)
The use of public debt is not new in financing developmental objectives. A significant challenge arose when it became obvious that the indebted countries could not fulfill its existing financial obligation to the rest of the world where debt is sourced. For a panel of 4 heterogeneous countries from 1990 to 2017, we study governments' reactions to debt accumulation and the corrective measures taken when its borrowings result in a rise in debt-GDP ratio. The study evidence is based on the fixed effect and the feasible generalized least squares estimators. We find evidence that primary balance improves by about 0.005-0.013 for every 1 percentage point increase in central government debt after controlling for other relevant factors. The results further suggest that the accrued interest payments on debt reflect the effective debt management policies across the countries, whereas the activities on the current account balance impose a possible threat to the primary balance. The study calls for policies that increase fiscal bases through the reduction in fiscal expenditure and the reinforcement of tax base revenue across the MIST countries.
Keywords: 650